2022
DOI: 10.26552/com.c.2022.3.b189-b198
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Unit for Reducing the Toxicity of Diesel Vehicle Exhaust Gases

Abstract: The article presents materials on use of ultrasonic waves to reduce the smoke and toxicity of diesel engine exhaust gases. The results of the experiments are presented. The hypothesis on the reduction of smoke and toxicity of the exhaust gas due to the acceleration of the coagulation of its particles under the action of ultrasound has been confirmed. The dependences of the degree of turbidity of a diesel car on the number of revolutions of the engine crankshaft per minute and the dependence of the content of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It can be concluded that the optimal operating parameters of the full-size stand determined during the experiments correspond to the ultrasonic frequency of 40 kHz in all values of the crankshaft speed. These parameter values correspond to the condition of the criterion of optimal operation of the ultrasonic muffler and provide a minimum value for the ratio of the exhaust gas indicators [48][49][50][51][52]. The diagram in Figure 12 shows that with an increase in the value of f/ω, the ratio of the flue gas indicators decreases.…”
Section: Parameters Valuementioning
confidence: 99%
“…It can be concluded that the optimal operating parameters of the full-size stand determined during the experiments correspond to the ultrasonic frequency of 40 kHz in all values of the crankshaft speed. These parameter values correspond to the condition of the criterion of optimal operation of the ultrasonic muffler and provide a minimum value for the ratio of the exhaust gas indicators [48][49][50][51][52]. The diagram in Figure 12 shows that with an increase in the value of f/ω, the ratio of the flue gas indicators decreases.…”
Section: Parameters Valuementioning
confidence: 99%
“…In practice, the following methods of exhaust gas purification are used: dry, wet, electric, catalytic and ultrasonic methods [6]. Until now, no electric gas purification method has been used in car mufflers [7]. There are a number of patents that propose the creation of a special chamber for electric air purification placed between the engine collector and the muffler [8,9].…”
Section: Introductionmentioning
confidence: 99%